ANALISIS VERBA HASIL REDUPLIKASI DALAM NOVEL BERJUDUL ORANG-ORANG BIASA - Aswarini Sentana; Ratna Wulandari (Asosiasi Dosen Muda Indonesia, 2023)
This is linguistic research that analyzes verbs resulting from reduplication in a novel. The aim of this research is to determine the grammatical meaning of verbs resulting from reduplication in the novel entitled Orang-orang Biasa. In conducting this research, the researchers used descriptive qualitative methods through library research. The results of this research show that the grammatical meanings of the verbs resulting from reduplication in the novels analyzed are (1) actions carried out without a specific purpose, (2) repeated or continuous actions, (3) reciprocal action, (4) actions with high intensity, and (5) possessiveness or ownership. The results of the analysis also show that the second meaning, namely repeated or continuous actions, dominates the grammatical meaning of the verbs resulting from reduplication in the novel under study. This means that reduplication produces verbs that tend to express actions that are repeated or carried out continuously.